The legality of the United Nations humanitarian intervention under Chapter VII of the UN Charter: Somalia and beyond. - Osman Haji, Abdiwahid. (University of Ottawa (Canada), 1999)
The UN Charter acknowledges the right of the UN Security Council to use force to address threats to international peace and security in case of acts of aggression. The Charter, however, does not expressly recognize the right to use force to protect the people of a State against their own governing authorities even when they face genocide, massive internal and external displacements of population, widespread violence, and mass starvation. In the post-Cold War era, the UN Security Council has authorized humanitarian intervention in Iraq (1991), in Somalia (1992), in the Former Yugoslavia (1992), and in Rwanda (1994). Although the cases each involve different circumstances, they share one momentous motive, that the Security Council determined that human rights violations in these countries had consequences which threatened international peace and security and thus, the Council invoked the provisions of Chapter VII of the UN Charter. These interventions have raised difficult questions of whether the UN Security Council's actions in cases of humanitarian crises or in cases of massive human rights abuses within a territory of a member state are legal under Chapter VII of the UN Charter or whether the Security Council's competence to use force under Chapter VII of the Charter is confined to cases of military aggression. The purpose of this thesis is to demonstrate that under Chapter VII of the UN Charter the UN has the legal right to intervene for humanitarian purposes in the internal affairs of a member State. This thesis focuses on the Security Council interventions involving internal armed conflicts in which widespread human rights violations occur, with particular analysis of the Somalia crises. It concludes that current international law recognizes the legality of UN humanitarian intervention under Chapter VII of the UN Charter.
Keywords: Political Science, International Law and Relations.